The Role of Customer Value as Intervening in Repurchase Decisions: The Case of Skincare Indonesia - Panjaitan, Feliks Anggia Binsar Kristian; Panjaitan, Hotman (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: Companies can more easily communicate product information by using digital marketing. Indonesian manufacturers of skincare products use digital marketing to advertise and promote their goods to a larger target audience. The objective of this study is to assess the potential mediating role of customer value in the relationship between digital marketing, product quality, brand perception, and the decision-making process of repurchasing products. Methodology: A quantitative research approach using purposive sampling of 210 research respondents from the population of Indonesian skin care product consumers based in Surabaya. Analysis was carried out using structural equation models, with Warp PLS 5.0 software.Finding: The results demonstrate that customer value does not mediate the relationship between digital marketing and repurchase decisions. The influence of brand perception and product quality on decisions to repurchase goods is mediated by customer value. Research findings also indicate that in comparison to digital marketing, factors such as product quality and brand image have a favorable impact on customer value. Conclusion: It is important to assess and improve how skin care products are marketed and promoted online. Brand perception, product quality, and customer value can increase customer repeat purchases. These findings have implications for the skin care business and highlight the need to prioritize factors that contribute to customer value to drive sales and increase customer repurchase decisions.